Žiznʹ i smertʹ v aušvickom adu - Poljan, Pavel Markovič, 1952- 1952- (Istorija de-fakto, 2018)
"History of the Holocaust / Nazi genocide, the Auschwitz-Birkenau concentration camp and killing center, papers and evidence victims burried there that have been discovered after the war, which were previously unknown in Russian; and the Sonderkommando, victims the Nazis forced to assist with the murders... about 110 of about 2,200 sonderkommando survived, and several dozen of them wrote about their experiences or gave detailed interviews...." --